Fast reactor core and fuel structural behaviour proceedings of the international conference organized by the British Nuclear Energy Society held in Inverness on 4-6 June 1990. (British Nuclear Energy Society, 1990)
This is an analysis and exchange of information about the structural behaviour of fast reactor cores and core components. The book covers the range of the design, development, safety and in-service aspects of core and fuel structural performance.